Simulation study on the performance of MAC protocols on wireless networks - Goh, Roney Boon Hui. (2008)
The FAFS (Fair Access Fair Scheduling) protocol is a newly proposed MAC protocol for Wireless ATM. It can be classified as a Demand Assignment Protocol, a sub-category of Centralized Hybrid MAC Protocols, as there is a Base Station (BS) controlling a group Mobile Terminals (MTs).